Analisis percepatan waktu menggunakan metode Crashing pada Proyek CWI-02 ITS Surabaya - Yahya, Fandy Ahmad Amiruddin; Beatrix, Michella (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In the implementation of construction projects, the measure of project success can be seen from the timely completion time at minimal cost without forgetting the quality of the work. This study aims to determine the duration of the project after acceleration and to know the cost after acceleration. This research was conducted on the CWI-02 ITS Surabaya project. According to the results of existing data in the field, the project has a delay of 8.8879%, so the way to overcome the delay is one of them using the Crashing method, with the alternative of adding working hours and adding labor. The results of the calculation by adding working hours for 4 hours obtained the project duration to 291 or 0.01% faster than the total project of 294 days, then there was a change in the total project cost of Rp. 3,622,264,104.66 or 0.0057% greater than the total project cost. While the calculation results with alternative labor additions obtained the project duration to 292 or 0.0068% faster than the total project duration, then there was a change in the total project cost to Rp. 3,600,758,240.47 or 0.03% greater than the total project cost.